PENDIDIKAN BISNIS MEMASUKI ERA MILENIUM BARU TANTANGAN DAN HARAPAN - Rohimah Rohimah (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2018)
As we enter the new millennium, business schools or economics faculties face a number of new challenges. The graduates of a business school are expected to be critical capable of 'learning to learn', technology-savy, and ethical. Mean while, the emergence of the internet as a new and powerful communication infrastructure has facilitated the rapid growth of the virtual business schools around globe. It leads to the global completion among processes, services, universies. As a consequence, Indonesian universies have to reform its products, processes, services, people, and environments. one of the 'best' approaches to do so is the adaptation of total quality management consep into higher education environment. This paper describes the profiles of future alumni of business schools, followed by a discussion on the emergence of virtual business schools as a new business education paradigm in the future. Finally, this paper tries to identify sereval factors critical to the successful implementation of total quality management in universities.